THE ISSUE OF CREATING AN EXPLANATORY DICTIONARY OF TELEPHONE COMMUNICATION NETWORK TERMS AND REGULATING TERMS - Mahmudova Nilufarxon Tolkinjon kizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article will talk about the implementation of practical work on the regulation of telephone communication network terms in Uzbek linguistics, the creation of an Explanatory Dictionary of terms used in the field.